Steroid administration facilitates recovery in severe refractory Bell’s palsy patients who did not receive steroids in the acute stage: a retrospective study - Ding, Sha-Sha; Song, Kai-Hua; Zhang, Ying-Ying; Xu, Fu; Xuan, Li-Hua; Hong, Shou-Hai (Frontiers in Neurology, 2026)
BackgroundIn the present study, we aimed to evaluate the efficacy of steroid treatment on patients with severe refractory Bell’s palsy in the recovery stage who had not been treated with steroids in the acute stage.MethodsWe performed a retrospective analysis of 122 patients with severe refractory Bell’s palsy. These patients had a clinical course of 15–30 days, House-Brackmann (HB) grade ≥ IV, and no history of steroid therapy. Of those, 65 patients who received steroid therapy after hospitalization were assigned to the steroid group and 57 patients who did not receive steroid therapy were assigned to the control group. Both groups received folic acid and mecobalamin, acupuncture, and mirror exercises as basic treatments. The primary outcome was the rate of grade I on the HB Grading Scale. The secondary outcome was the Sunnybrook Facial Grading system. All outcomes were assessed before treatment (baseline), at 2 weeks of steroids treatment (2 weeks), and at 8 weeks after steroids treatment (10 weeks).ResultsThe steroid group had a better recovery rate of facial-nerve function than the control group (p < 0.05).ConclusionThe use of steroids facilitate the recovery of severe refractory Bell’s palsy in the recovery stage, who did not receive steroids in the acute stage.